2004
DOI: 10.1242/jcs.00948
|View full text |Cite
|
Sign up to set email alerts
|

The 12 kDa FK506-binding protein, FKBP12, modulates the Ca2+-flux properties of the type-3 ryanodine receptor

Abstract: 2+ stores is mainly mediated by two distinct families of tetrameric intracellular Ca 2+ -release channels, ryanodine receptors (RyRs) and inositol 1,4,5-trisphosphate receptors (Ins(1,4.5)P3Rs) (Berridge et al., 2000). Both channels are encoded by three different genes, leading to the expression of three different isoforms. The activity of these channels is tightly regulated by a plethora of cellular factors, such as Ca 2+ , pH, redox state, ATP and associated proteins (Mackrill, 1999;Patel et al., 1999;Bultyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…In addition, a proposed binding site for the 12-kDa and 12.6-kDa FK506-binding proteins [FKBP12 and FKBP12.6 (also known as FKBP1A and FKBP1B, respectively)] on the different RyR isoforms is located within the binding domain for Bcl-2 on the RyRs identified in this study (Brillantes et al, 1994;Bultynck et al, 2001b;Gaburjakova et al, 2001;Marx et al, 2000;Van Acker et al, 2004). Both FKBP12 and FKBP12.6 are immunophilins that are tightly associated with the RyR and are necessary for stabilizing the channel (Brillantes et al, 1994).…”
Section: Discussionmentioning
confidence: 86%
“…In addition, a proposed binding site for the 12-kDa and 12.6-kDa FK506-binding proteins [FKBP12 and FKBP12.6 (also known as FKBP1A and FKBP1B, respectively)] on the different RyR isoforms is located within the binding domain for Bcl-2 on the RyRs identified in this study (Brillantes et al, 1994;Bultynck et al, 2001b;Gaburjakova et al, 2001;Marx et al, 2000;Van Acker et al, 2004). Both FKBP12 and FKBP12.6 are immunophilins that are tightly associated with the RyR and are necessary for stabilizing the channel (Brillantes et al, 1994).…”
Section: Discussionmentioning
confidence: 86%
“…2322-2323), the Ile-Pro dipeptide at position 2427-2428 in RyR2, the leucylprolyl residue in IP 3 R1 (amino acids 1400-1401), and the type-1 receptor of transforming growth factor b (amino acids [193][194] have been shown to be crucial residues for FKBP binding, and the binding of FKBP to these proteins can regulate their activation (Charng et al, 1996;Cameron et al, 1997;Marx et al, 2000;Gaburjakova et al, 2001;Van Acker et al, 2004). These specific peptidylprolyl epitopes structurally resemble FK506 (Cameron et al, 1997), which explains the ability of FK506 to attenuate the interaction between the peptidylpropyl residue and FKBP12.…”
Section: Fkbp12 and Morphine-induced Pkc« Activationmentioning
confidence: 99%
“…In these experiments, the FKBP and pc-MycRyR2C plasmids were co-expressed in HEK293 cells, and evidence for binding was monitored by assaying the amount of FKBP cosedimenting with the microsomal membrane fraction. Centrifugation-based binding assays are often used in situations of rapid ligand dissociation and low affinity, because the receptor and ligand remain in equilibrium throughout the separation period, and they have been used for the study of the RyR-FKBP association (27,29,43,44), as well as the RyR-calmodulin interaction (45). In addition, the assay takes place in a detergent-free environment where the RyR2 C-terminal fragment is most likely to retain a native conformation.…”
Section: Ryr2 C-terminal Fragments Compete For Fkbp126mentioning
confidence: 99%
“…However, the early biochemical evidence indicated that FKBP binds to a short, central portion of the RyR, mapping to amino acids 2407-2520 for RyR1 (26) and at amino acids 2361-2496 for RyR2 (16), as identified with the yeast two-hybrid assay. Further support for this central location was provided by mutational analysis in full-length RyR1 (22,27) and RyR3 channels (28,29) expressed in HEK293 cells followed by assessment of FKBP12/12.6 binding by co-immunoprecipitation or GST-FKBP affinity chromatography. These studies identified Val-2461 in RyR1 (and the corresponding Val-2322 in RyR3) as an important residue for FKBP binding.…”
mentioning
confidence: 99%